Perancangan Mortar Geopolimer Abu Sekam - Januar Fitri; Monita Olivia; Iskandar Romey S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study present about geopolymer mortar with rice husk ash (RHA) as binder. Both material are used their silica element were activated by alkaline solution. Alkaline solution was prepared by combining sodium silicate and sodium hydroxide of 18 M. Compressive strength of geopolymer mortar that was studied based variation of modulus activator, dosage activator, curing time, and curing temperature. Research showed that optimum mix proportion of geopolymer mortar with Rice Husk Ash (RHA) which result the optimum compressive strength. The ratio of sodium silicate solution to sodium hydroxide solution by mass was 2.5:1. The mass ratio of alkaline solution to blended ashes was 9:10. Test specimens 5×5×5 cm cube were prepared and cured at room temperature (28ºC) for 3 days and heat-cured at 70ºC for 24 hours. The speciemens were cured at room temperature for 7 days until testing date. Result from this research represents compressive strength the mortar as according to variation molar of sodium hydroxide and used a little addition of water.Keywords: Rice Husk Ash, Geopolymer, Alkali Activator, dosage activator.